Slow pyrolysis of orange peels blended with agro-food wastes: characterization of the biochars for environmental applications - Kordoghli, Sana; Fassatoui, Emna; Largeau, Jean François; Khiari, Besma (Comptes Rendus. Chimie)
The main objective of this research is to explore the viability of adequate blends of orange peels with some abundant bio-wastes, such as date pits, peanut shells, coffee grounds, and tea waste, to generate bio-chars while applying a thermal pyrolysis process. It was revealed that pure orange peels lead to a high biochar yield (32.05%). The different blends with orange peels did not show significantly increased char output. However, the biochar yields were lower with coffee grounds and date pits, which shows the positive effect of blending with orange peels for these two biomasses as far as char is concerned. However, the blends appeared to favour syngas production with yields as high as 56% for the coffee grounds and orange peels blend. FTIR and SEM characterizations indicated that recovered solids could represent a viable source of carbon materials, biofertilizers, or solid fuels.